Community Participation and Preparedness for Integrating Disaster Risk Reduction (DRR) in Managing Disasters A Study of Srinagar Floods (2014), India - Zutshi, Bupinder (European Scientific Journal, ESJ, 2020)
Sendai Framework of Action has emphasized on, community participation and preparedness, as a major strategy for Disaster risk-reduction (DRR), for managing disasters. It ensures that, effects of disasters are minimized and people are made, resilient for improved coping capacities, to attain resettlement at the earliest. Jammu & Kashmir state experienced worst flood, during first week of September 2014, due to unprecedented and incessant rains and existing flood vulnerabilities. A total of 1.16 million population, out of 1.27 million population, of Srinagar Urban Agglomeration were, affected by the September 2014 floods. Present study, attempts to examine flood vulnerabilities and steps taken, by Jammu & Kashmir, State Disaster Management Authorities (SDMA) and NGOs, for reducing identified flood vulnerabilities and creating conducive conditions, for adopting community participation and preparedness measures, to integrate disaster risk reduction strategies. The study is based on both secondary and primary sources of information. Secondary sources of information include, government measures adopted for reducing flood vulnerabilities. A primary field survey was conducted, among the flood affected families, to study community participation, preparedness and perception changes, in adopting Disaster Risk Reduction measures. Findings, from the study, indicate, that State machinery has been created for implementing Disaster-risk-reduction measures and community participation and preparedness has been sufficiently activated. However, awareness generation measures, like safety audits, implementation of building codes and development of emergency resettlement centres, are not effectively working. Although early warning system equipment, have been installed, but people are not aware, as to how, such warning will be communicated and what measures are required during warning period.